2012
DOI: 10.2147/cia.s25215
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of influenza vaccine in aging and older adults: comprehensive analysis of the evidence

Abstract: Foremost amongst the diseases preventable by vaccination is influenza. Worldwide, influenza virus infection is associated with serious adverse events leading to hospitalization, debilitating complications, and death in elderly individuals. Immunization is considered to be the cornerstone for preventing these adverse health outcomes, and vaccination programs are timed to optimize protection during the annual influenza season. Trivalent inactivated influenza virus vaccines are believed to be both effective and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 80 publications
3
69
1
11
Order By: Relevance
“…Comprehensive reviews come to differing conclusions dependent on study design, methodology, inclusion criteria and varying approaches to the correction of season-to-season variation of vaccine matching 35,43,44 . Two large meta-analyses assessing the same body of evidence have come to differing conclusions, whilst one group concluded that there was insufficient evidence with respect to older adults 42 , the other concluded when virus was circulating, vaccination reduced influenza-related and non-fatal complications by 28% and confirmed cases of influenza by 5% 45 .…”
Section: Older Adultsmentioning
confidence: 99%
“…Comprehensive reviews come to differing conclusions dependent on study design, methodology, inclusion criteria and varying approaches to the correction of season-to-season variation of vaccine matching 35,43,44 . Two large meta-analyses assessing the same body of evidence have come to differing conclusions, whilst one group concluded that there was insufficient evidence with respect to older adults 42 , the other concluded when virus was circulating, vaccination reduced influenza-related and non-fatal complications by 28% and confirmed cases of influenza by 5% 45 .…”
Section: Older Adultsmentioning
confidence: 99%
“…Old people remain poorly vaccinated in Europe but effectiveness of vaccination is also known to decreases with age, whether it is due to immuno-senescence or to interactions with the common chronic comorbid conditions of the oldest-old people [7]. Furthermore, it should be noted that a large proportion of the oldest old people live in nursing homes and other collective households.…”
Section: In This Issue Aging Clinical and Experimental Researchmentioning
confidence: 99%
“…Berdasarkan data dari berbagai penelitian tersebut, nampaknya proses priming atau paparan antigen vaksin berulang menjadi dasar yang penting dari keberhasilan vaksin terkait imunogenesitasnya. 22 …”
Section: Diskusiunclassified